Human resources efforts to improve employee performance at JW Marriott Surabaya - Shenia Dwi Virdanty; Nyoman Mastiani Nadra; Ni Made Sudarmini; Ni Wayan Wahyu Astuti; Ni Made Rai Erawati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Human resources are the first elements of an organization. This study aims to find out and analyze the efforts made by the human resource (HR) department in improving the employee performance of JW Marriott Surabaya. This research was conducted to Human Resources, they are Assistant HR and Training Manager and Human Resources Coordinator took using Purposive Sampling technique, which is considered to know the efforts to improve employees’ performance. Data collection techniques by using observation, interviews, documentation, and studies literature. Data analysis in this study uses a qualitative method with technical triangulation analysis. The results showed that performance improvement efforts began with, employee placement, training and development, discipline in employee attendance, and the provision of salaries and compensation to employees but the need for supervision, multiplying variants of methods in training, and acting decisively to employees who are less disciplined to existing regulations.